Е. К. Редин – секретарь Харьковского предварительного комитета по подготовке ХІІ Археологического съезда - Филиппенко, Р. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
E.K. Redin - Secretary of Kharkiv preliminary committee for the preparation of XII Archaeological Congress